LINGUOPOEIC STUDY OF THE RELATIONSHIP OF IDIO STYLE AND STYLISTIC CONVERGENCE (Scientific journal of the Fergana State University, 2024)
The article provides information about new approaches to the study of linguistic phenomena that have emerged in linguistics in recent years, and focuses on the anthropocentric approach, which is considered one of the modern directions and methods of linguistic analysis. At the same time, the author’s unique style of speech creativity – idiostyle – is assessed as a product of an anthropocentric approach. In the methodological analysis of linguistic means, it is impossible to determine the author's idiostyle without paying attention to their functionalization for a specific purpose in speech, norms of word usage, the originality of the formation of syntactic devices, and also without paying attention to narration. It has been proven that the author's idiostyle is a complete reflection of the system of linguistic means of the native language, and at the same time, the author's idiostyle serves as a source of enriching the language with new units and means. Also, stylistic convergence, formed as a result of the joint use of several syntactical and stylistic means, and the phenomenon as a sign of the author's idiostyle, as well as issues of stylistic changes in the structure and the impact of the artistic and aesthetic function of speech, are considered.